2020
DOI: 10.1038/s41598-020-77428-w
|View full text |Cite
|
Sign up to set email alerts
|

Arousal influences olfactory abilities in adults with different degree of food neophobia

Abstract: Food neophobia, i.e., the aversion to novel foods, and olfaction are both factors strongly affecting food choices. Mounting evidence suggests a higher arousal towards food as a key factor underlying the reluctance to eat what is unfamiliar to us. As the role of olfaction behind this phenomenon is poorly understood, we explored the associations between food neophobia and trait anxiety, olfactory functions (odor threshold, discrimination and identification) and retronasal aroma release from a reference food in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…High-neophobic subjects gave lower liking scores to the mint and pine odors and lower perceived intensity scores to the banana and pine odors. These results are in accordance with the studies conducted by Raudenbush and colleagues [ 38 ] and Menghi and colleagues [ 40 ], which showed that neophobic individuals rated the evaluated odors as less pleasant and perceived them less intensely. A possible explanation of these findings lies in the caution that neophobic subjects put on trying novel olfactory stimuli.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…High-neophobic subjects gave lower liking scores to the mint and pine odors and lower perceived intensity scores to the banana and pine odors. These results are in accordance with the studies conducted by Raudenbush and colleagues [ 38 ] and Menghi and colleagues [ 40 ], which showed that neophobic individuals rated the evaluated odors as less pleasant and perceived them less intensely. A possible explanation of these findings lies in the caution that neophobic subjects put on trying novel olfactory stimuli.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, Demattè et al [ 18 ] showed that neophobics were less able in odor identification than neophilics. However, Menghi et al [ 40 ] concluded that the conflicting relationship between neophobics and new food may be led by higher levels of arousal toward foods, rather than different chemosensory functions.…”
Section: Introductionmentioning
confidence: 99%
“…Older people or those with lower education tend to have a higher level of food neophobia (Soucier et al., 2019 ). Fear related to unpleasant sensory cues of (novel) food is the key factor to refuse new food (Menghi et al., 2020 ). Flight et al.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, olfactory abilities and FN are strongly linked. Indeed, high-neophobics tend to evaluate an odor as less intense and less pleasant than neophilics (Raudenbush et al, 1998), and they show an overall worse olfactory performance than neophilics as measured by the TDI (odor Threshold, Discrimination and Identification) score obtained with the Sniffin' Sticks battery (Hummel et al, 1997, Menghi et al, 2020. Moreover, high-neophobic individuals also exhibited increased anxietyrelated physiological responses and a lower extent of retronasal aroma release during the consumption of a strawberry jelly candy.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, high-neophobic individuals also exhibited increased anxietyrelated physiological responses and a lower extent of retronasal aroma release during the consumption of a strawberry jelly candy. These phenomena might be explained by the tendency of neophobics to avoid unpleasant food-related experiences (Menghi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%